Theoretical treatment and computer simulation of microelectrode arrays - Morf, Werner E.; Koudelka-Hep, Milena; de Rooij, Nicolaas F. (My University, 2006)
New relations for and interrelations between the current responses of different microelectrode arrays are presented. Interdigitated microelectrode arrays (IDAs: alternating cathodes and anodes) and uniform microband electrode arrays (MEAs: only cathodes or anodes) are treated, and miniaturized systems with planar band electrodes or hemicylinder electrodes are discussed. A common basis was found for the specific response characteristics of IDAs and MEAs. The theoretical expressions were verified by results from computer modelling. The numerical simulations made use of finite-element procedures to evaluate steady-state and time-dependent mass fluxes and concentration profiles of electroactive species at the surfaces of different microelectrode arrays. It was shown that the response behavior of a given array can be exactly predicted from the current data of other arrays.
Keywords: Microelectrodes; Interdigitated electrode array; Current response; Concentration profiles; Theory; Computer simulation; Finite-element method